Clinical features, microbial co-detection profiles, and 28-day mortality of carbapenem-resistant Klebsiella pneumoniae pneumonia: a retrospective study with mNGS-based resistance gene detection - Yonggang Liang; Xinjing Fu; Huan Xu; Lingling Cui; Zhe Xing; Jianglong Ren; Hua Xiao; Pengju Lv; Shoukui Hu (BMC Infectious Diseases, 2026)
Abstract Background Pulmonary infections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) are associated with high mortality. In this study, the clinical characteristics, microbial co-detection profiles, and outcomes were compared between CRKP and carbapenem-susceptible Klebsiella pneumoniae (CSKP) patients. Moreover, metagenomic next-generation sequencing (mNGS) was performed for resistance gene detection, and risk factors for 28-day mortality in CRKP patients were identified. Methods In this study, 158 patients with K. pneumoniae pulmonary infection (81 patients with CRKP and 77 patients with CSKP) were retrospectively included. Clinical data, laboratory findings, and pathogen profiles were compared between the two patient groups. The diagnostic performance of mNGS was evaluated against culture-based antimicrobial susceptibility testing (AST). LASSO regression and multivariable logistic regression were conducted to identify independent risk factors for 28-day mortality in CRKP patients. Results The baseline characteristics were similar between the groups. Patients with CRKP more frequently suffered from dyspnea (53.1% vs. 35.1%, P = 0.034) and had a higher number of white blood cells ( P = 0.035). The mNGS-based co-detection of additional microorganisms, especially Acinetobacter baumannii , was significantly more common in CRKP patients than in CSKP patients (43.2% vs. 24.7%, P = 0.022). The mNGS results demonstrated an overall accuracy of 93.06% and a sensitivity of 87.65% for carbapenem resistance gene detection, with blaKPC identified as the predominant resistance gene ( n = 72). CRKP infection was associated with significantly higher mechanical ventilation rates ( P < 0.001), longer ICU stays ( P = 0.001), and greater in-hospital mortality (27.2% vs. 6.5%, P = 0.001). Fibrinogen (OR = 0.45, P = 0.019) and IL-6 (OR = 1.08 per 100-unit increase, P = 0.036) were identified as independent predictors of 28-day mortality in CRKP patients. Conclusions Pulmonary infection caused by CRKP imposes a significant disease burden, characterized by higher rates of microbial co-detection, increased resource utilization, and higher mortality compared to CSKP. The mNGS technique serves as a complementary strategy to conventional diagnostics for detecting carbapenem resistance genes. Fibrinogen and IL-6 serve as clinically accessible biomarkers to stratify the risk associated with 28-day mortality in CRKP patients.